Sustainable Transport and Potential Mobility - Black, William R. (European Journal of Transport and Infrastructure Research, 2002)
Any index that seeks to assess transport sustainability for areas will soon confront the problem that these areas must also have some reasonable level of mobility. Implicitly the impacts on sustainability are the least where the economy has not yet developed. As a result there is a need to explicitly consider the level of potential mobility that the economy is capable of supporting. An index is proposed here that is based on the difference between the level of sustainability and the level of potential mobility, standardized for population size and units of measurement. The index is illustrated for a number of different policy and regulatory situations. More important than the index developed are the limitations of this or other measurement systems in this area. These range from how one can allocate aviation fuels to specific countries to how one can translate current environmental targets into index values. There will have to be considered in the development of any future indices in this area.